WSi2 nanodot reinforced Si particles as anodes for high performance lithium-ion batteries. Issue 39 (21st September 2020) - Zhou, Xiangyang; Luo, Chucheng; Ding, Jing; Yang, Juan; Tang, Jingjing
Abstract : Si-based anodes are attracting enormous attention due to the super-high theoretical capacity of silicon (3579 mA h g −1 at room temperature) as an anode of lithium-ion batteries. Abstract : Si-based anodes are attracting enormous attention due to the super-high theoretical capacity of silicon (3579 mA h g −1 at room temperature) as an anode of lithium-ion batteries. Extensive efforts have been made to explore various composite structures to enhance the electron transmission performance throughout the anodic electrodes and improve the cycling stability. However, the obtained electrochemical reactivity of the Si anode is still limited due to the low conductivity of Si. To address this issue, we exploit a novel approach to embed highly conductive WSi2 nanodots within Si nanoparticles (WSi2 /Si). In this structure, WSi2 nanodots (2–5 nm) are well-dispersed within an irregular Si matrix with a primary particle size of 30–70 nm that can facilitate the electron transport, thereby enhancing the electronic conductivity and improving the electrochemical reaction activity, and thus achieving high capacity and good rate performance. As a result, the WSi2 /Si composite shows a high electrical conductivity of 1.613 S cm −1 compared with non-doped Si with 1.182 × 10 −5 S cm −1 . The WSi2 /Si composite exhibits superior electrochemical performance, including an initial charge capacity of 2001.2 mA h g −1 at 0.84 A g −1 and a high capacity retention of 75.2% after 200 cycles. In addition, the WSi2 /Si composite exhibits an excellent cycling stability of 903.4 mA h g −1 over 1000 cycles at 4.2 A g −1 . Even at a high rate of 6.72 A g −1, a reversible capacity of 692.6 mA h g −1 can be maintained. Remarkably, the lithiation-induced volume change of the Si matrix is effectively alleviated due to the well-dispersed WSi2 nanodots within the Si matrix. This work could provide a valuable reference for preparing highly conductive Si via a simple and scalable method as a starting material for preparation of high performance Si-based composites.